A STUDY OF SATISFACTION WITH PRENATAL CARE SERVICES IN THE WOMEN ATTENDING TO THE HEALTH CENTERS OF THE SHIREVAN CHARDAVEL (IRAN), IN 2005 - M. Danesh Kojuri; S. Karimi; R. Shekarabi; F. Hossinei (Iran University of Medical Sciences, 2005)
One the most important aspect of quality of prenatal care, is satisfaction among clients. In fact the main goal of prenatal care is giving birth, with a healthy newborn without complication.   In this study, the objective was to determine satisfaction of pregnant women attending to the health center that receive prenatal care.   The design of the study was cross-sectional descriptive. The sample size was 460 subjects (338 pregnant women and 122 women in their postpartum period). The sampling method was census selection. The instrument for data collection was a questionnaire, consists of the items of demographic characteristics, satisfaction of prenatal care services and its' quality. The study setting was 54 small health canters in shire van chardavel district.   The study results showed that the majority of the subjects (89.8%) had high and very high satisfaction with the timetable of the prenatal care, whereas 10.2% had low and very low satisfaction. Regarding prenatal care facilities, 79.8% of the subjects had high and very high satisfaction and only 20.2% of the subjects had low and very low satisfaction. Approximately 93.6% of the women had high and very high satisfaction in relation to the communication of the prenatal care personnel, whereas 6.3% had low and very low satisfaction about 60.2% sixty percent of the women who participated in the current study, had low and very low satisfaction with the received prenatal care information whereas 39.8% had high and very high satisfaction. House wives and employees in had, more satisfaction with the timetable. The rate of satisfaction during first pregnancy (P=0.035) and in the your women (P=0.027) were high.   According to the study findings, the majority of the subjects were satisfied with the received prenatal care, though 60.2% of the women were unsatisfied regarding the information of the prenatal care.   Apparently there is a necessity to update the prenatal care providers' knowledge. It is recommended that more studies should be conducted regarding the barriers of raising the awareness and giving appropriate information to the women in prenatal clinics.